'Dover Beach' and the uncertain afterlife of Victorian environments. Issue 2 (2nd April 2020) - Feder, Helena
ABSTRACT: Ian McEwan was among the writers, historians, and philosophers from twenty-one countries who signed a letter published last year in papers across Europe that warned of the rising tide of anti-liberalism and ersatz-populism threatening 'disdain for intelligence and culture; explosions of xenophobia and antisemitism; disaster.' One signatory, Orhan Pamuk, said, 'Without the idea of Europe, freedom, women's rights, democracy, egalitarianism is hard to defend in my part of the world' (Henley and Rice-Oxley). Fifteen years earlier, Paul Gilroy's Postcolonial Melancholia decried the waning of international solidarity 'in the era of actually existing internationalism which has perversely created an environment where cosmopolitanism and translocal affiliations became suspect and are now virtually unthinkable outside of the limited codes of human-rights talk, medical emergency, and environmental catastrophe' (5). In the years since, the contradiction has only sharpened. This perverse internationalism—neoliberal global capitalism coupled with the rise of various right-wing nationalisms—has gone a fair way to eliminating the social environment in which even climate change and the mass extinction of plants and animals matter across borders. While on the right side of this moment in history, both McEwan and Gilroy have thought quite a lot about Matthew Arnold's iconic 'Dover Beach' in this context and, in their different ways, got it rather wrong. In this context, that of the last few hundred years and its relation to the last few decades, I will examine 'Dover Beach' and the afterlife of its Victorian environments. The Dover poet's exclamatory turn to romantic love in stanza four is not simply an 'inward turn' away from public concerns, a 'defensive gesture' against warfare and turbulence as Gilroy argues. Our individual and collective need for love, an insistence on this truth, and those that follow from it, is, I will argue, always social and has real political value.